Ответы и объяснения

2011-11-19T17:20:24+00:00

3x=-12

х=-4

 

1/6x=-2/3

х=-2/3:1/6

х=-2/3*6/1

х=-12/3

х=-4

 

5x=4

х=4/5

 

-3/4x=-9

х=-9:-3/4

х=-9*-4/3

х=36/3

х=12

 

7x=-1.4

х=-1.4/7

 

2/3x=-8

х=-8:2/3

х=-8*3/2

х=-24/2

х=-12

 

2011-11-19T17:22:41+00:00

1) 3x = -12

x = -12 / 3

x = -4

2) 2/6x = -2/3

x = -2/3 : 2/6

x = -2/3 · 6/2

x = -6/3

x = -2

3) -5x = 4

x = -4/5

x = -8/10

x = - 0,8

4) -3/4x= -9

x = -9 : (-3/4)

x = 9 · 4/3

x = 12

5) 7x = -1,4

x = - 14/10 : 7

x = - 14/10 · 1/7

x = - 0,2

6) 2/3x= -8

x = -8 : 2/3

x = -8 · 3/2

x = -12